Efektifitas Tindakan Frenektomy Pada Bayi Tongue Tie Dengan Kemampuan Menyusu - Hesty Tri Kurniasari; Kristina Maharani; Siti Juwariyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Tongue tie cases at the Columbia Asia Surgical Hospital in Semarang in the last two years have experienced an increase, where in 2021 there were 438 cases and in 2022 there were 447 cases. Tongue tie babies have a poor breastfeeding mechanism, this is caused by limited tongue movement, so tongue tie babies cannot attach properly when breastfeeding. These conditions result in the maximum intake of breast milk not being obtained and the mother feeling uncomfortable due to sore nipples which can cause premature cessation of breastfeeding. This study aims to analyze the effectiveness of frenectomy in tongue tie babies with breastfeeding ability. This research is a type of quasi-experimental research with a one group pretest-posttest design. The population in this study were tongue-tie babies without complications who were still being hospitalized at the Columbia Asia Surgical Hospital in Semarang. Using a purposive sampling technique, a sample of 30 babies was obtained. The instruments used in this study were LATCH and ATLFF scores. Data analysis was performed using univariate analysis and bivariate analysis. The results of the study showed that the Frenectomy procedure was effective in increasing the ability to suckle in tongue tie babies, the Wilcoxon test results were obtained (pvalue 0.000 <0.05), where all (100%) tongue tie babies experienced an increase in the ability to suckle after a frenectomy. The action of a frenectomy is effective in increasing the ability to suckle, this can be due to the fact that with a frenectomy the mobility of the tongue increases, so that the baby can latch on properly, can swallow milk well, the mother feels comfortable while breastfeeding because the nipples are not painful.